Disturbance‐rejection voltage control of an isolated microgrid by invariant sets. Issue 13 (14th September 2020) - Bayoumi, Ehab; Soliman, Mostafa; Soliman, Hisham M.
Abstract : New disturbance‐rejection control for an islanded microgrid (MG) is presented in this study. The proposed method can be used with MGs consisting of several distributed generation (DG) units and local loads with both grid‐connected and islanded modes capability. The proposed controller utilises state feedback with integral control to track the desired voltage. The uncertainty of the load parameters is tackled as a disturbance. The proposed controller is designed using the method of invariant ellipsoids to guarantee robust stability, fast transient response and zero steady‐state error. The controller synthesis is formulated as a convex optimisation problem that is effectively solved using linear matrix inequality methods. The performance of the proposed MG voltage controller is assessed by several simulations in the presence of random load variations, load unbalances and step changes in the voltage reference. Moreover, the power mismatch during accidental islanding event is also considered.